Isenção administrativa Carmelitana : a procura por autogestão dentro da Ordem Terceira do Carmo em Minas Gerais (XVIII-XIX) - Felipe Augusto de Bernardi Silveira (2017)
The present work analyze the behavior denominated Self-management that shapes the administrative and institutional performance of the Third Order of Carmo during the second half of the 18th century to the end of the 19th century in Minas Gerais. It occurs in the performance of the Administrative Table, in the internal functioning and relations before the Catholic Church, First Order of Carmo and Imperial State within the region of Minas Gerais. The proposal of this research is to construct a new field of studies and historiographical interpretations, that welcomes the Carmelite third institutions before the frame of economic, political and social singularities initiated from 1746 to 1891. Through the practice " Self-management " of the Third Order of Carmo de Minas Gerais, we analyze the forms of diachronic adaptability responsible for remodeling the contours of the administrative organization, the statutes, funeral practices, the information network and assistencialism among the Third Orders of Carmo.